Comic impostors of Ukrainian and Russian literature in the end of the 18th – first half of the 19th centuries - Ніколова, Олександра Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article deals with the specific of the use of characters-impostors’s variants as the comic methods in Ukrainian and Russian literature in the end of the 18th – first half of the 19th centuries. We make a comparative analysis on the basis of synthesis of contact-genetic and typological methods. We define variations of comic impostors: pseudoinspectors, pseudonoblemen, pseudorichmen, bridegrooms-impostors, king-impostor of G. Kvitka-Osnovyanenko and psevdoheroes of A. Pushkin and N. Yazykov. We prove, that writers use these images for comic effect’s creating: for criticism of human and social disadvantages, parody transformation-modernization of narrative clichés, intrigue’s creating, amplification of dynamic plot. We make conclusions about the specifics of imagery concretization of imposture in Ukrainian and Russian literature in the end of the 18th – first half of the 19th centuries and its relationship with the thematic contexts.